2011
DOI: 10.1589/jpts.23.773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motion Strategies in the Functional Reach Test between Elderly Persons and Young Persons

Abstract: Evaluation of motion strategy during FRT is not generally included in physical assessment aiming at rehabilitation and promotion of good health. We believe that measuring only reach distance during FRT is insufficient for evaluating gait; therefore, examining motion strategy during FRT is also necessary. [Subjects] The subjects were 83 healthy university students (46 men and 37 women; range, 19-21 years), and 128 elderly persons (42 men and 86 women; range, 70-87 years). [Methods] We investigated and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Balance performance was measured using the functional reach test (FRT) 16 ) . The researchers chose the FRT as it demonstrates the maximal distance a person can reach forward beyond arm’s length while maintaining a fixed based of support in standing position; the FRT also serves as an index of fall risk 17 ) . Participants were instructed to stand with their feet shoulder distance apart, make a fist, and raise their arm to be parallel with the floor.…”
Section: Methodsmentioning
confidence: 99%
“…Balance performance was measured using the functional reach test (FRT) 16 ) . The researchers chose the FRT as it demonstrates the maximal distance a person can reach forward beyond arm’s length while maintaining a fixed based of support in standing position; the FRT also serves as an index of fall risk 17 ) . Participants were instructed to stand with their feet shoulder distance apart, make a fist, and raise their arm to be parallel with the floor.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the studies that performed movement strategies used during the FRT, Takasaki et al [ 14 ] used a video camera, while Waroquier–Leroy et al [ 15 ] and Wernick–Robinson et al [ 16 ] have used a force plate and a three-dimensional motion analysis system. Takasaki et al [ 14 ] and Wernick–Robinson et al [ 16 ] have classified movement strategies during the FRT based on ankle and hip movements, whereas Waroquier–Leroy et al [ 15 ] used cluster analysis to divide two similar groups. These studies demonstrated the importance of the ankle and hip movements, but the relationship between the FRT values and the COPE was not examined.…”
Section: Introductionmentioning
confidence: 99%